Deliberate self-harm by gender among adolescents: a comparative analysis study among junior high school students - Rani Mega Putri; Khadijah Lubis; Nur Wisma; Siti Nurhaliza; Putri Setiawati (Institute of Advanced Engineering and Science, 2026)
Self-harm is an increasingly common phenomenon among adolescents. This can include cutting the skin, hitting oneself, or harming the body in other ways, which is generally done in response to emotional distress or inability to manage stress. This study aims to identify self-harm behavior among adolescents and analyze the differences in self-harm between male and female adolescents. The sample in this study consisted of 600 junior high school students in Palembang City selected using simple random sampling (SRS) techniques. The instrument used is the self-harm inventory (SHI) questionnaire developed by the researcher and has a reliability of 0.93 (very good). Data analysis used descriptive statistics and independent sample t-tests. The results showed that adolescents’ self-harm behavior was in the very low category (mean=42.11, SD=12.70), and there was no significant difference in the self-harm of adolescent boys and adolescent girls (Sig. equal variance=0.711). Nevertheless, counseling teachers in schools must take preventive actions to prevent self-harm behavior in adolescents.